Analisis Realisasi Pemungutan Pajak Hotel dan Pajak Restoran Terhadap Pendapatan Asli Daerah (PAD) di Kota Manado - Moningka, Petrus; Ariani, Richter (JBE (Journal of Business and Economics); Volume 10 No.1, 2011 JBE UNKLAB, 2011)
This research has the purpose to know how big the realization growth of Hotel and Restaurant taxes of Manado city, the rate of Hotel and Restaurant taxes to local per capita (PAD) of Manado City, also its signification to Local per capita of Manado City.  Using the secondary data as a consolidated tax return DISPENDA of Manado City in 2003-2010.  By using the simple linear regression to know the tax effect of Hotel and Restaurant tax to the local per capita. This research outcome indicates that the growth for Hotel tax is 21.28% and Restaurant tax is 26.23% and local per capita is 18.21%, the contribution of Hotel tax is smaller as compared to Restaurant tax, and thel last, Hotel and Restaurant taxes have a significant effect to local per capita of Manado City.